Level Pemberian Tepung Rosella (Hibiscus sabdariffa Linn) Terhadap Kualitas Dendeng Babi - Sipahelut, Geertruida Margareth; Armadianto, Heri; Noach, Yakob R.; Riwu, Agustinus R.; Dillak, Sutan Y.F.; Riwu, Junius Rede Lae (Fakultas Peternakan Universitas Papua, 2021)
The purpose of this research to determine the level on the quality of pork jerky (aroma, texture and TPC). The research design used was a complete random design (CRD) with 4 treatments and 3 replications, and continued with Mann-Whitney test. The sensoric data used hedonik test according to Kruskal-Wallis method. The treatment consisted of R0 = without roselle flour, R1 = roselle flour 5g, R2 = roselle flour 10g and R3 = roselle flour 15g. The results showed that the addition of roselle flour 5g, 10g and 15g gave a significant difference (P <0.05) to the aroma and TPC values while the texture had no significant effect (P>0,05). But the best texture value is at the level of 10g roselle flour. Conclusion, The level of roselle flour influences the value of the aroma of jerky and can reduce the total bacterial growth in the pork jerky. The best activity level of 15g roselle flour can reduce the lowest total bacterial colony.